Peningkatan Mutu Organoleptik Keripik Pisang Produksi Kelompok Wanita Tani di Desa Neglasari - Afifah Nurmaimanah; Prayoga Suryadharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Farmer Women Group, or known as KWT, is one of the groups engaged in processing post-harvest products. There are 4 main products produced by KWT, namely cassava chips, banana chips, pikong, and candied nutmeg. The biggest production is banana chips. The problem with